2021
DOI: 10.4014/jmb.2106.06039
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota of Breast Tissue and Its Potential Association with Regional Recurrence of Breast Cancer in Korean Women

Abstract: Recent studies have reported dysbiosis of the microbiome in breast tissue collected from patients with breast cancer and the association between the microbiota and disease progression. However, the role of the microbiota in breast tissue remains unclear, possibly due to the complexity of breast cancer and various factors, including racial and geographical differences, influencing microbiota in breast tissue. Here, to determine the potential role of microbiota in breast tumor tissue, we analyzed 141 tissue samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The content of breast microbiota might have value in discriminating patients who are at higher risk of regional recurrence, as shown by Kim et al. ( 67 ). Of note, Porphyromonas , Lacibacter , Ezakiella , and Fusobacterium were more abundant in higher-stage versus lower-stage tumors.…”
Section: Role Of Commensal Bacteria In Bc Growth and Progressionmentioning
confidence: 93%
“…The content of breast microbiota might have value in discriminating patients who are at higher risk of regional recurrence, as shown by Kim et al. ( 67 ). Of note, Porphyromonas , Lacibacter , Ezakiella , and Fusobacterium were more abundant in higher-stage versus lower-stage tumors.…”
Section: Role Of Commensal Bacteria In Bc Growth and Progressionmentioning
confidence: 93%
“…Oncobiosis is also associated with disease recurrence. Kim et al reported that when comparing patients with high and low risk of regional recurrence of breast cancer, bacterial pentose and glucuronate interconversions and Enterococcus were the main discriminating factors [95]. In support of these observations, antibiotic overdosing can increase the likelihood of disease recurrence [29].…”
Section: The Role Of Oncobiosis In Metastasis Formation Survival and Recurrence In Breast Cancermentioning
confidence: 94%
“…Tzeng, et.al (2021) [12] 16S rRNA sequencing HER2+, ER+ 57 Fresh-frozen breast cancer tumor Proteobacteria, with either Firmicutes or Actinobacteria Shi, et.al (2019) [13] 16S rRNA sequencing HER2+, ER+, -Frozen fecal sample of breast cancer patient Actinobacteria Bacteroidetes, firmicutes, Fusobacteria, Proteobacteria Hieken, et.al (2022) [14] 16S rRNA sequencing ER+ 60 Benign and malignant breast tissue Firmicutes, staphylococcus Dubigeon, et. al (2021) [15] 16S rRNA sequencing HER2-, ER+ 63 Fecal microbiota breast cancer patient Firmicutes, Clostridium Blautia Kim, et.al (2021) [16] 16S rRNA sequencing ER+ (59,6% [17] 16S rRNA sequencing --Stool specimen of malignant breast Escherichia, Peptoniphilus, Bilophila, Lactobacillus, and Porphyromonas Lasagna, et.al (2022) [18] 16S rRNA sequencing ER/PR+ and HER2-Stool specimen from breast cancer patient…”
Section: Methodsmentioning
confidence: 99%